E-Cigarette Users’ Attitudes on the Banning of Sales of Nicotine E-Liquid, Its Implication on E-Cigarette Use Behaviours and Alternative Sources of Nicotine E-Liquid - Wong, Li Ping; Alias, Haridah; Aghamohammadi, Nasrin; Ghadimi, Azadeh; Hoe, Victor Chee Wai (Springer, 2017)
The banning of sales of nicotine e-liquid in e-cigarette shops has been implemented in several states in Malaysia. The distribution of nicotine e-liquid can only be allowed by licensed pharmacies or registered medical practitioners. This study aimed to evaluate e-cigarette users’ responses to the control policy in a cross-sectional survey of 851 e-cigarette users by utilizing a self-report questionnaire that assessed (1) attitudes on regulation policy of e-cigarette banning; (2) e-cigarette use behaviors; and (3) sources of e-liquid after the regulation policy has been implemented. Participants from the state of Selangor where the banning policy was implemented were surveyed. The majority (95.8%) opposed the banning and believed e-cigarettes should be sold to anyone aged 18 years or above as with tobacco cigarettes, only a minority believed that nicotine e-liquid should only be available for sale over the counter in pharmacy stores (14.6%) and in clinics with a doctor’s prescription (11.8%). The majority (44.2%) reported that they would continue their e-cigarette use as before the banning policy, while 20% plan to completely stop e-cigarette usage without replacing it with any alternatives. The vast majority (87.9%) was still able to obtained nicotine e-liquid from e-cigarette shops in spite of the ban and the second most common source was from online purchase (63.1%). The sales of nicotine e-liquid from black-market were evidenced as many reported obtaining zero nicotine e-liquid from the black market (54.4%). Self- or home-made (30.8%) nicotine e-liquid was also reported. Majority of respondents that self-made e-liquid were from the average monthly income group (below MYR3000). Obtaining nicotine from the pharmacy was least preferred (21.4%). Provision of professional advice to nicotine e-liquid users along with the ban may lessen the likelihood of users switching to tobacco cigarettes or other nicotine alternatives. Banning of sales of nicotine e-liquid in e-cigarette shops resulted in a boom in the black market supplying nicotine e-liquid and, self- or home-made nicotine e-liquid. Enforcing regulations and monitoring black market sales is warranted. Efforts to educate e-cigarette users of the danger of sourcing nicotine e-liquid from the black market and self- or home-made nicotine e-liquid are essential.